Celebrating 90 years of Science Education: Reflections on the Gold Standard and Ways of Promoting Good Research - Brickhouse, Nancy W. (Science Education, 2006)
Editorial of The International Journal of Science Education about how to promote good research.
Keywords: politique éducative; utilisation des recherches; États-Unis